Analisis Hukum Batas Kewenangan Pemerintah Daerah dalam Pemungutan Pajak dan Retribusi Daerah - Abdul Rojak; Aturkian Laia (INDO PUBLISHING, 2026)
Local fiscal autonomy positions regional taxes and retributions as key instruments for independence, yet this authority is constrained by the principle of a unitary state. The enactment of Law No. 1/2022 (UU HKPD) significantly alters the boundaries of local government authority in managing local revenues. Utilizing a normative legal research method with statutory and conceptual approaches, this study analyzes the legal basis, boundaries, and judicial implications of these limitations. The findings reveal that while local authority originates from Article 18 of the 1945 Constitution, it is strictly limited by a closed-list system, draft regional regulation evaluations, and central government tariff controls. Consequently, these restrictions reduce regional flexibility and create tension between fiscal decentralization and centralized control. This study recommends harmonizing UU HKPD implementing regulations to ensure balanced local authority without hindering local revenue optimization.